Influence of solvents on Aloe vera gel performance in dye-sensitized solar cells - Gossen, Katrin; Storck, Jan Lukas; Ehrmann, Andrea (Optik)
Dye-sensitized solar cells (DSSCs) can be prepared from non-toxic, low-cost materials outside a cleanroom, opposite to common silicon-based cells. Especially for large areas, such as textile architecture, they can be used due to the aforementioned advantages. On the other hand, their efficiencies are very low if no specialized dyes – which are typically toxic and expensive – are used. This is why a broad variety of natural dyes has been investigated during the past decades. Here we report on aloe vera gel extracts, prepared with different solvents, as sensitizers for DSSCs. We show the dependence of the UV/Vis spectra on the solvents as well as the time-dependent electrical properties of the resulting DSSCs. Our results underline the influence of the solvent on the dye extraction and the corresponding DSSC efficiencies.